The role of training in improving employability, job satisfaction and the career success of public sector employees - Marzec, Izabela; Austen, Agata (Publishing House of Wroclaw University of Economics and Business, 2021)
The importance of knowledge for the success of modern organizations results in growing interest in the issue of the professional development and the employability of public sector employees. Constant development and professional training are necessary. This situation poses a serious challenge for many employees, affecting their job satisfaction and opportunities for career success. The paper attempted to answer the question of what are the relations between training and professional development, and employability, job satisfaction and the subjective career success of public sector employees? This goal was achieved by examining the results of surveys conducted in public sector organizations. The results indicate that employee training and development positively influence employability, as well as employee career success and job satisfaction. Moreover, the positive impact of job satisfaction on subjective career success was identified.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 187-204
Keywords: emplyability; professional development; training; job satisfaction; career success; public organizations